Governance in mental healthcare policies during the COVID-19 pandemic in Mexico - Diaz-Castro, Lina; Suarez-Herrera, Jose Carlos; Gonzalez-Ruiz, Oscar Omar; Orozco-Nunez, Emanuel; Sanchez-Dominguez, Mario Salvador (Frontiers in Public Health, 2023)
The COVID-19 pandemic has become the greatest burden of disease worldwide and in Mexico, affecting more vulnerable groups in society, such as people with mental disorders (MD). The aim of this research is to analyze the process of governance in the formulation of policies for care for people with MD in the face of the COVID-19 pandemic. A qualitative observational study of analytical nature was conducted, based on semi-structured interviews with key informants of the health system, during 2020. The study adhered to the theoretical-methodological principles of the Governance Analytical Framework (GAF). ATLAS.ti-V.9 was used for inductive thematic analysis, classifying topics and their categories, taking into account the constituent elements of governance and discussing discrepancies and emerging codes. Coding ended when all data was organized into core topics, categories, and subcategories. To ensure the proper interpretation of the data, a triangulation process was carried out among the researchers. The findings revealed that in Mexico, the federal Secretary of Health issued guidelines for mental healthcare, but there is no defined national policy. Decision-making included multiple actors, with different strategies and scopes, depending on the type of key-actor and their level of power. The infection control policies in psychiatric population were the same to general populations which decreased the percentage of access to healthcare during the pandemic, with no specific measures to address this vulnerable population.